Pengaruh Pemberian Buku Saku Demam Berdarah Dengue Terhadap Penurunan Kepadatan Jentik Nyamuk Aedes Aegypti L. Di Kelurahan Gedongkiwo Mantrijeron Kota Yogyakarta - Suksesi, Tri Wahyuni; Shela, Bayu (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT The environment is very bad Gedongkiwo Village and unhealthy. The condition of every corner of the house a lot of small pools of unused, used items such as paint cans scattered, small aquariums, buckets of water reservoirs and many other items that may be a nest to lay eggs of Aedes sp. This is what causes the density of mosquito larvae in high Gedongkiwo Village area. The objective of this study was to know the impact of the provision of a paperback book Dengue Fever to decrease the density of larvae of Aedes sp in Gedongkiwo Village, District Mantrijeron, Yogyakarta. This research is a quasi experimental. The population in this study is the number of homes that are on RT 17 and RT 18 as many as 48 houses with a total sample of 43 homes. Analysis of the data in this study using univariate analysis to obtain an overview of each independent variable and the dependent variable and using bivariate analytical hypothesis test between two variables with independent variables and the dependent variable. Giving pocket book turned out to give effect to the dengue mosquito larvae density that can be seen from the value of HI, Cids BI.